DETERMINANTS OF FIRM VALUE: SUSTAINABILITY REPORT AS A MEDIATING VARIABLE - Monika Indah Cahyani; Dwi Suhartini (Yayasan Education and Social Center, 2023)
This study aims to investigate the impact of Corporate Social Responsibility (also known as CSR) and Good Corporate Governance (also known as GCG) on Firm Value using Sustainability Report as a mediating variable. This investigation into the relationships between variables makes use of quantitative research techniques. The number of samples that can be processed is 40 data from 8 mining companies listed on Indonesia Stock Exchange (IDX) in 2017-2021. The data used in this study are the company's annual report, financial statements, and sustainability report. The results of this study indicate that CSR has no effect on firm value, and sustainability reports cannot mediate the relationship between CSR and firm value. In addition, the high implementation of GCG has yet to respond to the increase in company value or sustainability report. A sustainability report can partially mediate the relationship between GCG and firm value, and implementing a sustainability report can increase firm value. It shows that mining companies in Indonesia have supported the noble ideals of SDGs responsible for environmental and future corporate sustainability